A fluoroplastic cable material and its preparation method and application
By performing aminosilane surface modification treatment on PFA material, the problems of its high melting point, viscosity and porosity are solved, and the application is realized in high humidity environments and is suitable for high-temperature cable insulation layers.
Patent Information
- Application Number
- CN202311828771.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-12-28
AI Technical Summary
The high melting point, viscosity and surface hydrophilicity of PFA fluoroplastic materials lead to difficult processing and high porosity, limiting their application in high humidity environments.
The tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer is surface modified by aminosilane to reduce surface tension and viscosity, and to reduce porosity through specific preparation methods.
It significantly reduces the porosity after extrusion molding, improves processing smoothness, and makes fluoroplastic cable materials suitable for cable insulation layers in high humidity and high temperature environments.
Smart Images

Figure BDA0004635795310000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable materials, in particular to a fluoroplastic cable material and a preparation method thereof. Background Art
[0002] Tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer (PFA) is a melt-processed fluoroplastic with excellent heat resistance, chemical corrosion resistance and mechanical properties. It can be used as the insulation layer of cables or wires in some special fields.
[0003] However, PFA also has certain shortcomings. Compared with other conventional plastics, its melting point is relatively high and its viscosity is high. During the melt extrusion process, special processing equipment is usually required, so the cost of PFA is relatively high. At the same time, the surface energy of PFA material is relatively low, which leads to its good hydrophilicity. The hydrophilicity of the surface makes it very susceptible to the influence of water vapor in the environment during the processing, and eventually pores are easily formed in the extruded product. This problem greatly limits the application of PFA material in some high-humidity environments.
[0004] In view of this, providing a PFA fluoroplastic cable material that can reduce surface pore defects has become one of the technical problems that need to be solved urgently. Summary of the invention
[0005] In view of this, the present invention proposes a fluoroplastic cable material and a preparation method and application thereof, aiming to reduce the porosity in the fluoroplastic cable.
[0006] The technical solution of the present invention is achieved as follows: the present invention provides a fluoroplastic cable material, the raw materials of the fluoroplastic cable material are calculated by weight and include: 70-80 parts of aminosilane modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer, 8-12 parts of carbon black, 1-2 parts of dispersant, 1-2 parts of antioxidant and 4-6 parts of filler.
[0007] In some embodiments, the preparation method of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer comprises the following steps:
[0008] (1) crushing tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer to an average particle size of 2-3.5 mm;
[0009] (2) heating the crushed tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer to 120-140° C. for vacuum drying, and after drying to constant weight, introducing oxygen plasma for surface plasma treatment for 30-60 seconds;
[0010] (3) preparing an ethanol solution of aminosilane, immersing the plasma-treated tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer in the ethanol solution of aminosilane for 1-3 minutes, filtering and drying to constant weight, and obtaining an aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0011] In some embodiments, the aminosilane is 3-aminopropyltrimethoxysiloxane or 3-aminopropyltrimethylsiloxane.
[0012] In some embodiments, the mass concentration of the aminosilane ethanol solution is 4-8%.
[0013] In some embodiments, the dispersant is sodium lauryl sulfate.
[0014] In some embodiments, the antioxidant is triphenylphosphonic acid.
[0015] In some embodiments, the filler is talc.
[0016] On the other hand, the present invention also provides a method for preparing a fluoroplastic cable material, comprising the following steps:
[0017] Step 1: weigh each raw material by weight and dry it to constant weight, then add it into a mixer, heat it to 260-270°C under an inert atmosphere, and stir and mix it at a speed of 20-30 rpm for 10-30 minutes;
[0018] Step 2: Extruding the mixed material through an extruder to granulate it to obtain cable material.
[0019] The fluoroplastic cable material of the present invention can be used for the insulation layer of high-temperature furnace cables.
[0020] The fluoroplastic cable material of the present invention has the following beneficial effects compared with the prior art:
[0021] The present invention adopts aminosilane to carry out surface modification treatment on granulated tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer, which not only reduces the surface tension of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer, reduces the amount of water vapor mixed in the processing process, and reduces the porosity in the material after extrusion molding, but also after the surface modification of aminosilane, the viscosity of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer is reduced to a certain extent, the extrusion process is smoother, and the surface porosity is lower. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.
[0024] Example 1
[0025] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0026] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0027] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0028] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0029] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0030] Example 2
[0031] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0032] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2.5 mm were prepared, dried in a vacuum drying oven at 120° C. to constant weight, and then the dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0033] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0034] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0035] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0036] Example 3
[0037] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0038] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 3 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0039] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0040] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0041] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0042] Example 4
[0043] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0044] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 3.5 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0045] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0046] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0047] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0048] Example 5
[0049] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0050] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 140° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 60 seconds, with stirring during the treatment process.
[0051] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0052] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0053] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0054] Example 6
[0055] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0056] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0057] Prepare 1L of 6% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0058] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0059] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0060] Example 7
[0061] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0062] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0063] Prepare 1L of ethanol solution of 3-aminopropyltrimethoxysiloxane with a mass concentration of 8%, and immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the ethanol solution of 3-aminopropyltrimethoxysiloxane for 1 minute, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0064] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0065] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0066] Example 8
[0067] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0068] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0069] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 2 minutes, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0070] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0071] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0072] Example 9
[0073] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0074] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0075] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 3 minutes, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0076] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0077] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0078] Example 10
[0079] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0080] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0081] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0082] Take 800g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 120g of carbon black, 20g of sodium dodecyl sulfate, 20g of triphenylphosphoric acid and 60g of talc, dry to constant weight, add into a mixer, heat to 270°C under an inert gas atmosphere, rotate at 30rpm, and stir and mix for 10min.
[0083] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0084] Embodiment 11
[0085] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0086] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0087] Prepare 1L of 4% 3-aminopropyltrimethylsiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer.
[0088] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0089] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0090] Comparative Example 1
[0091] Preparation of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer modified by methylsilane:
[0092] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0093] Prepare 1L of 4% methyltrimethoxysilane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer particles after surface plasma treatment in the ethanol solution of methyltrimethoxysilane for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain methylsilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer.
[0094] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0095] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0096] Comparative Example 2
[0097] Preparation of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer modified by acrylic silane:
[0098] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0099] Prepare 1L of ethanol solution of trimethoxysilane acrylate with a mass concentration of 4%, and immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the ethanol solution of trimethoxysilane acrylate for 1 minute, then filter and dry in a vacuum dryer to constant weight to obtain methylsilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0100] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0101] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0102] Comparative Example 3
[0103] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0104] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 1 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0105] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0106] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0107] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0108] Comparative Example 4
[0109] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0110] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 4 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0111] Prepare 1L of 4% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0112] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0113] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0114] Comparative Example 5
[0115] Take 700g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0116] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0117] Comparative Example 6
[0118] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0119] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0120] Prepare 1L of 3% 3-aminopropyltrimethoxysiloxane ethanol solution, immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the 3-aminopropyltrimethoxysiloxane ethanol solution for 1 min, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0121] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0122] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0123] Comparative Example 7
[0124] Preparation of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer:
[0125] 1000 g of tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles with an average particle size of 2 mm were prepared, and the medium was dried at 120° C. in a vacuum drying oven to constant weight. The dried tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles were then transferred to a plasma treatment chamber, and oxygen plasma was introduced into the surface of the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles under a nitrogen atmosphere for plasma treatment for 30 seconds, with stirring during the treatment process.
[0126] Prepare 1L of ethanol solution of 3-aminopropyltrimethoxysiloxane with a mass concentration of 10%, and immerse the tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer particles after surface plasma treatment in the ethanol solution of 3-aminopropyltrimethoxysiloxane for 1 minute, then filter and dry in a vacuum dryer to constant weight to obtain aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer.
[0127] Take 700g of aminosilane-modified tetrafluoroethylene-perfluoroalkoxyvinyl ether copolymer, 80g of carbon black, 10g of sodium dodecyl sulfate, 10g of triphenylphosphoric acid and 40g of talc, dry to constant weight, add into a mixer, heat to 260°C under an inert gas atmosphere, rotate at 20rpm, and stir and mix for 30min.
[0128] Then the mixed material after the kneading treatment is extruded and granulated through an extruder to obtain a cable material.
[0129] The cable materials prepared in the above embodiments and comparative examples were used for the basic production of cable insulation layers, and the tensile yield strength and maximum traction composite of the cable materials were tested according to GB / T 8804.1. At the same time, the porosity of the insulation layer of the above-obtained cable was tested by water saturation method. The test results are as follows:
[0130]
[0131] It can be seen from the above embodiment data that the cable material prepared by the preparation method of the fluoroplastic cable material of the present invention not only has good mechanical properties, but also the porosity of the obtained cable material is greatly reduced. The cable material prepared using the above cable material can be used for cable insulation layers in some high-humidity and high-temperature environments.
[0132] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A fluoroplastic cable material, characterized in that: The raw materials of the fluoroplastic cable material are calculated by weight: 70-80 parts of aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer, 8-12 parts of carbon black, 1-2 parts of dispersant, 1-2 parts of antioxidant and 4-6 parts of filler; the preparation method of the aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer comprises the following steps: (1) crushing tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer to an average particle size of 2-3.5 mm; (2) heating the crushed tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer to 120-140° C. for vacuum drying, and after drying to constant weight, introducing oxygen plasma for surface plasma treatment for 30-60 seconds; (3) preparing an ethanol solution of aminosilane, immersing the plasma-treated tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer in the ethanol solution of aminosilane for 1-3 minutes, filtering and drying to constant weight, and obtaining an aminosilane-modified tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer; The aminosilane is 3-aminopropyltrimethoxysiloxane or 3-aminopropyltrimethylsiloxane, and the mass concentration of the ethanol solution of the aminosilane is 4-8%.
2. The fluoroplastic cable material according to claim 1, characterized in that: The dispersant is sodium lauryl sulfate.
3. The fluoroplastic cable material according to claim 1, characterized in that: The antioxidant is triphenylphosphonic acid.
4. The fluoroplastic cable material according to claim 1, characterized in that: The filler is talc.
5. The method for preparing the fluoroplastic cable material according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: weigh each raw material by weight and dry it to constant weight, then add it into a mixer, heat it to 260-270°C under an inert atmosphere, and stir and mix it at a speed of 20-30 rpm for 10-30 minutes; Step 2: Extruding the mixed material through an extruder to granulate it to obtain cable material.
6. Use of the fluoroplastic cable material according to any one of claims 1 to 4 in high temperature furnace cables.
Citation Information
Patent Citations
Fireproof flame retardant fluoroplastic cable material and preparation method thereof
CN107254128A
